BOYCOTT, DIVESTMENT, AND SANCTION (BDS): LABA BERSIH DAN ARUS KAS, TERHADAP HARGA SAHAM PADA PERUSAHAAN TERDAMPAK - Rakhmawati, Aida; Amelia, Yuni (Jurnal Riset Akuntansi Politala, 2025)
This study aims to determine the simultaneous and partial influence of Net Profit and Cash Flow variables on Stock Prices in Primary and Non-Primary Consumer Goods Companies on the Indonesia Stock Exchange Affected by the Israeli Boycott Action for the 2019-2023 period. The population in this study amounted to 287 companies listed on the Indonesia Stock Exchange in the primary and non-primary consumer goods sector. The sample in this study was 6 companies with a purposive sampling method. The type of data used is secondary data in the form of company financial reports published by the Indonesia Stock Exchange and using multiple linear regression analysis techniques. The results of this study indicate that in companies affected by BDS, net profit partially affects stock prices and cash flow does not affect stock prices. Simultaneously, net profit and cash flow affect stock prices.